Analisis Kualitas Air Hujan Di Manokwari Yang Disaring Dengan Menggunakan Sistem Penyaring Sederhana - Rudyanita Lestari, Romadhoni; Afkril, Baina; M. G. Sadsoeitoeboen, Bernadetta (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Manokwari Regency is located in a tropical climate zone that experiences high rainfall in the rainy season so that it has the potential as an area for rainwater harvesting. Rainwater can be used as a source of clean water through rainwater harvesting by applying a filter system. This study aims to design a simple rainwater filtration system and analyze the quality of the filtered rainwater. The filter system is designed using layers of natural materials, in order from top to bottom are gravel, sand, charcoal and juk. Filtered rainwater samples for 3 different rain events were taken for quality testing based on physical parameters and chemical parameters. The results showed that physically, the filter system was able to reduce suspended material (TSS) in rainwater, however, the mineral content in the filter material contributed greatly to the increase in dissolved solids (TDS). Chemically, water passing through the filter system has a consistent increase in concentration of pH, nitrate, iron and sulfate parameters, but is able to reduce hardness and ammonia content In terms of quality, all filtered rainwater samples are still in the clean water quality standards and drinking water standards according to Minister of Health Regulation No. 2 of 2023 and Government Regulation of the Republic of Indonesia No. 22 of 2021 concerning class I water quality standards annex VI, while for pure rain, the chemical content with ammonia parameters does not meet the standards of class I water quality standards annex VI of Government Regulation of the Republic of Indonesia No. 22 of 2021.